Pencarian Otentisitas Islam Liberal Di Indonesia - Masnun Tahir (Universitas Islam Negeri Mataram, 2006)
In the contemporary Islamic discourse in Indonesia, an Islamic movement initiated by a group of young muslim intelectuals emerged which offered a new paradigm in comprehending Islamic doctrines. The movement naming itself Jaringan Islam Liberal (JIL) carrys some jargons of modern life like pluralism, tolerance, inclussivism, freedom of thought, and human rights. Through sociological approach, this article shows that JIL has played a significant role in dinamizing Islamic discouse in Indonesia. JIL proposed the “individualism” of Islamic thought; it is called “individual autonomy” in Berger and Luckman’s term, and “Islamic liberalism” in Binder and Kurzman’s one. Some methodologies applied by JIL in promoting its ideas are ijtihad freedom, hermeneutics, reactualization of Islamic doctrines, and “al-muhâfazhah ‘alâ al-qadîm al-shâlih wa al-akhdzu bi al-jadîd al-ashlah”.